Crop Growth and Water Use Modelling of Upload Crops - . Hermantoro; . Pusposutarjo (Jurnal Keteknikan Pertanian, 2000)
Palawija is still used as secondary food in Indonesia. Some of palawija crops were source of the carbohydrate, and the others like a peanut and soybean are source of protein. The common palawija crops grown on upland area are soybean, peanut, green pea, and corn. The major constrains on development of upland area for agriculture purpose was water scarcity and availability data of crops water requirement. The objective of the research was to develop the crop growth and water use modeling, determining the transpiration coefficient and crop water requirement of upland crops.